IN NEW UZBEKISTAN, HUMAN VALUE IS A PRIORITY (Academia Science Repository, 2023)
Today, we are establishing a new state of Uzbekistan, a free civil society, based on populist and democratic principles. For this purpose, large-scale democratic reforms aimed at strengthening the political and legal foundations of our state and society, modernizing the country, strengthening the role of parliament and political parties, and public control in this process are being rapidly implemented.